Nanomaterials against intracellular bacterial infection: from drug delivery to intrinsic biofunction - Chen, Yinglu; He, Xiaoheng; Chen, Qiuhong; He, Yi; Chen, Fangman; Yang, Chao; Wang, Liang (Frontiers in Bioengineering and Biotechnology, 2023)
Fighting intracellular bacteria with strong antibiotics evading remains a long-standing challenge. Responding to and regulating the infectious microenvironment is crucial for treating intracellular infections. Sophisticated nanomaterials with unique physicochemical properties exhibit great potential for precise drug delivery towards infection sites, along with modulating infectious microenvironment via their instinct bioactivity. In this review, we first identify the key characters and therapeutic targets of intracellular infection microenvironment. Next, we illustrate how the nanomaterials physicochemical properties, such as size, charge, shape and functionalization affect the interaction between nanomaterials, cells and bacteria. We also introduce the recent progress of nanomaterial-based targeted delivery and controlled release of antibiotics in intracellular infection microenvironment. Notably, we highlight the nanomaterials with unique intrinsic properties, such as metal toxicity and enzyme-like activity for the treatment of intracellular bacteria. Finally, we discuss the opportunities and challenges of bioactive nanomaterials in addressing intracellular infections.